Economic, equity, and political trade-offs in energy transition in irrigation in Bihar, India - Durga, N.; Gaurav, S. (Elsevier, 2024)
Affordable and reliable energy is an important driver for improving access to irrigation in South Asia. Policies for improving electricity access and augmenting supply are likely to impact affordability and equity in irrigation access, especially in regions where agriculture is the mainstay of the economy. In this paper, we focus on the state of Bihar in eastern India to study trade-offs across economic, equity, and political dimensions of energy transition in irrigation. We argue that in the context of the nascent but steadily increasing solar-powered irrigation, a decentralised energy regime is techno-economically and socio-politically distinct from a conventional centralised grid supply. With different economic costs, governance issues, and varied incentives of stakeholders, there are significant trade-offs associated with the two pathways of energisation. We further assess the multidimensional trade-offs associated with the conventional ‘centralised’ and the modern ‘decentralised’ energy supply systems for irrigation to present a comprehensive understanding of the technical systems aiming to address economic development and livelihood security issues. We find that the life cycle costs (LCC) of centralised grid supply are not only higher than that of decentralised solar-powered irrigation (SIP) but also the LCC for grid supply has a high sensitivity to average cost to supply electricity (ACS). We also find that at lower pumping hours or lower average cost to supply (ACS), grid electricity is competitive compared to SIP, but with an increase in pumping hours, ACS or both, there is a considerable increase in the LCC of the grid connected pump, making SIP a more economical option. Furthermore, we augment the analysis using primary data on farmers to examine the economic, equity, and political trade-offs. By highlighting the complexities associated with the diffusion of decentralised energy solutions in irrigation, our findings provide useful insights for public policy related to energy transition in irrigation in India.